THEORETICAL AND PRACTICAL ASPECTS OF TRANSLATION: BRIDGING THE GAP BETWEEN LANGUAGE AND CULTURE - Abdullayeva Diyora,; Ahmedov A, (Ustozlar uchun, 2025)
This paper investigates the dual nature of translation as both a theoretical discipline and a practical skill. The study highlights the importance of translation in facilitating global communication and preserving cultural identity. It outlines the theoretical frameworks that guide translation decisions, and explores the impact of new technologies on the profession. The paper concludes that successful translation requires not only linguistic knowledge but also cultural sensitivity and adaptability.